Môi trường đa dạng và sự sáng tạo của nhân viên: Vai trò của kỹ năng sáng tạo và định hướng học tập - Bùi Thị, Thanh; Phan Quố, Tấn; Lê Công , Thuận; Phạm Tô Thục , Hân; Nguyễn Thụy Nhật, Nguyệt (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
The influence of working climate on employee creativity has been emphasized by previous researchers. However, research on the impact of diversity climate on employee creativity is limited. This study applied the social exchange theory and the Ability-Motivation-Opportunity (AMO) framework to test the impact of diversity climate on employee creativity, examine the mediating mechanism of creativity-relevant skills as well as the moderating role of learning orientation in this relationship. Structural equation modeling (SEM) was used to test the research hypotheses. The research results show that creativity-relevant skills mediate the relationship between diversity climate and employee creativity. Furthermore, learning orientation moderates this relationship. Therefore, this study offers new theoretical contributions and provides managerial implications for enhancing employee creativity.